The Effect Of E-Servqual & E-Promotion On The Purchase Decision Of Used Cars At Home Showrooms In East Jakarta - Rusmeidi; Fedianty Augustinah; Liling Listyawati; Damajanti Sri Lestari (International Journal of Business and Quality Research, 2025)
The development of digital technology has driven a transformation in marketing strategies and customer service, including in the used car sales sector. Home-based showrooms in East Jakarta have begun to utilize digital media to reach consumers more broadly. This study aims to examine the effect of e-Servqual and e-Promotion on used car purchasing decisions in home-scale showrooms. The research method uses a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires to 132 respondents who had purchased used cars through digital platforms. The analysis results show that both e-Servqual and e-Promotion have a significant effect on purchasing decisions, both individually and simultaneously. The R Square value of 0.599 indicates that the two independent variables explain 59.9% of the variation in purchasing decisions, while the rest is influenced by other factors outside the model. This finding confirms the importance of clear information, quick response, and attractive digital promotions in influencing consumer behavior. The conclusion of this study is that service and digital promotion are the main strategies that must be optimized by home-based showroom businesses in the face of increasingly competitive market competition.